Bounded solution of Cauchy type singular integral equation of the first kind using differential transform method - Abdulkawi, M. (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
In this paper, an efficient approximate solution for solving the Cauchy type singular integral equation of the first kind is presented. Bounded solution of the Cauchy type singular Integral equation is discussed. Two type of kernel, separable and convolution, are considered. The differential transform method is used in the solution. New theorems for transformation of Cauchy singular integrals are given with proofs. Approximate results are shown to illustrate the efficiency and accuracy of the approximate solution.